Posvátno v nových náboženských směrech - Vojtíšek, Zdeněk (Lidé města, 2003)
The majority usually perceives the new religious movements as marginal social groups and even doubts if their practice is genuinely religious. In spite of this fact, the adherents of new religious movements experience a full-value touch of the sacred. In this article, seven new religious movements are shortly characterised and related to spheres of the sacred that are typical for them: (1) the sacred place in the Grail movement, (2) the sacred time among the Czech converts to Buddhism, (3) the sacred person in one of Hindu tantric groups, (4) the sacred action performed among a neo-pagan group of Slavs, (5) the sacred object in the Scientology Church, (6) the sacred story in one Czech UFO-group and (7) the sacred language among the followers of one Christian missionary. In this way, the article shows that the world is divided between the sacred and the profane sphere in new religious movements in the similar way as in any other religion.